Enabled or Disabled: Is the Environment Right for Using Biodiversity to Improve Nutrition? - Hunter, Danny; Özkan, Isa; Moura de Oliveira Beltrame, Daniela; Samarasinghe, Wellakke Lokuge Gamini; Wasike, Victor Wafula; Charrondière, U. Ruth; Borelli, Teresa; Sokolow, Jessica (Frontiers in Nutrition, 2016)
How can we ensure that 9 billion people will have access to a nutritious and healthy diet that is produced in a sustainable manner by 2050? Despite major advances, our global food system still fails to feed a significant part of humanity adequately. Diversifying food systems and diets to include nutrient-rich species can help reduce malnutrition while contributing other multiple benefits including healthy ecosystems. While research continues to demonstrate the value of incorporating biodiversity into food systems and diets, perverse subsidies and barriers often prevent this. Countries like Brazil have shown that by strategic actions and interventions it is indeed possible to create better contexts to mainstream biodiversity for improved nutrition into government programs and public policies. Despite some progress, there are few global and national policy mechanisms or processes that effectively join biodiversity with agriculture and nutrition efforts. This perspective paper discusses the benefits of biodiversity for nutrition and explores what an enabling environment for biodiversity to improve nutrition might look like, including examples of steps and actions from a multi-country project that other countries might replicate. Finally, we suggest what it might take to create enabling environments to mainstream biodiversity into global initiatives and national programs and policies on food and nutrition security. With demand for new thinking about how we improve agriculture for nutrition, and growing international recognition of the role biodiversity, the 2030 Agenda for Sustainable Development presents an opportunity to move beyond business-as-usual, to more holistic approaches to food and nutrition security.